BEL413: Language Enhancement for the Health Sciences / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
This course is designed to develop the students’ ability to communicate effectively in the field of Health Science. Tasks and activities suggested are discipline-based involving the four skills of listening, speaking, reading and writing.